Effective Educational Media for Health Promotion to Preventing Cervical Cancer of Women Reproductive in 2019–2022: A Systematic Literature Review - Sudartinah .; Heru Subaris Kasjono; Fitriani Mediastuti (JURNAL KEBIDANAN KESTRA (JKK), 2022)
The incidence of cervical cancer is 23.4 per 100,000 population with an average death rate of 13.9 per 100,000 population, where about 50% of cervical cancer sufferers end up dying. WHO predicts that in 2030 there will be an increase in cervical cancer patients and other cancer sufferers in Indonesia up to seven times. Media education with health promotion is one of the primary prevention that can be done to prevent cervical cancer. This study aims to analyze the most effective educational media for health promotion in the prevention of cervical cancer in women of childbearing age in 2019 - 2022 based on a systematic literature review. Literature search was carried out systemically in four DOAJ databases, Google Scholar, PubMed and Science Direct with publications between April 2019 to April 2022. Results showed 17,931 articles were originally drawn from a systematic search of the literature. Of these, six articles matched the theme and inclusion criteria. Of the six articles included in the study, they had good methodological quality. Of the six articles, five articles used quasi-experimental research methods and one article used qualitative research methods. Three of the six articles on experimental research, including interventions with films, clearly stated that audiovisual media had a significant effect on increasing knowledge, attitudes and behavior about cervical cancer. Another article states that the types of educational media used are booklets, social media, one of which is Facebook